Dressings for advanced wound care - Tang, Sharon Lam Po (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
The book starts by helping the reader understand what advanced wound care is and the market size. It then explains how different types of wounds may require different environments to heal and how dressings can help in creating the right environment. It gives an overview of the various dressing technologies that are available to help manage wounds that are difficult to heal. It provides recent clinical evidence that support how well (or not) the technologies work, and also discusses on how such technologies are launched in the market. Finally, the book will highlight the current trends that may be directing the future of the advanced wound dressing sector.
Includes bibliographical references and index.
Keywords: Wound Healing; Wounds and Injuries; Bandages